Usage of the Educational Video by Students-Veterinarians Who are Studying Operative Surgery - Stepanov, Oleksandr (Pedagogical Discourse, 2021)
The training of veterinary surgeons, in conditions that do not allow for surgical intervention, requires the use of modern interactive teaching aids. These include educational surgical video. Providing auditory and visual perception of information, it has high informative character. Surgical video gives the opportunity to communicate to each student all the intricacies of the operation, without requiring its presence on it, allows you to demonstrate all stages of the process, being in the most comfortable point of perception. Watching a high-quality video that reproduces the dangerous work of a surgeon without risk completely helps to master the necessary material. Another important advantage of the educational video is that the student can view it on his own, in order to acquaint or repeat the material, as well as to store it on disk media. In the course of research, an analysis of scientific sources on the use of educational videos in higher education was conducted. In order to obtain data on the use of surgical video, by the students studying operative surgery, were used such sociological methods as surveys, observations, questionnaires. According to the data obtained in the study of operative surgery, all students use the abstract of classroom lessons and surgical video. 75% of them use the textbook and 25% of the surgical sites. However, among those who take information on surgical sites, 70% are looking for text materials and 30% are browsing photos and pictures. In preparation for a real operation, all students prefer a video showing the entire operation from beginning to end. With the educational purpose of such a movie would be to view ¾ of the students surveyed, and for others it is short enough. 50% of the students after the first review of the video tutorial on the topic in the lecture room at home look for similar materials and revisit them as well as download their media. The work opens the prospect of further research on the use of surgical video in the preparation of veterinary surgeons.